The Effects of Pretreatment of Giberellic Acid, Alpha Tocopherol and Ascorbic Acid on Germination in Maize Seeds (Global Journal of Science Frontier Research, 2021)
The present study was conducted to determine the effects of gibberellic acid (GA), alphatocopherol (Vitamin E) and ascorbic acid (Vitamin C) on germination in maize seeds. The seeds were subjected to priming with 250 ppm GA, 300 ppm alpha-tocopherol, 100 ppm ascorbic acid for 24 h. The seeds which has grown at 25°C and 60% mousture, germination rate, germination duration, germination speed, germination index, length of radicle and plumula, fresh and dry weight, relative water content, protein content and catalase enzyme activity were determined after 7 days. The results clearly revealed that GA application has an positive effects on the physiological and biochemical parameters in maize seeds. Otherwise, Vitamin E has a positive effect on germination whereas Vitamin C has a negative effects depending on the application dose. The results of GA and E applications were significiant but others were not.
Keywords: ascorbic asid; alpha-tocopherol; catalase; gibberellic acid; maize